2016
DOI: 10.1136/neurintsurg-2016-012745
|View full text |Cite
|
Sign up to set email alerts
|

Single-stage endovascular treatment of multiple intracranial aneurysms with combined endovascular techniques: is it safe to treat all at once?

Abstract: Single-stage endovascular treatment of multiple aneurysms with combined endovascular techniques is technically feasible and increases the treatment possibility of all detected aneurysms. However, the safety of the procedure is controversial due to relatively high complication rates. In particular, in patients with bilateral internal carotid artery aneurysms, staged therapy may be used instead of simultaneous treatment with flow diverters to avoid thromboembolic events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…3 Patients with multiple aneurysms have higher mortality and significantly poorer outcomes than those with a single aneurysm. 4 The treatment methods for IA include microsurgical clipping and endovascular embolization. The latter has gained major acceptance over time due to progress in endovascular techniques and the expertise of operators, as well as technological advances that have allowed improvement in long-term outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Patients with multiple aneurysms have higher mortality and significantly poorer outcomes than those with a single aneurysm. 4 The treatment methods for IA include microsurgical clipping and endovascular embolization. The latter has gained major acceptance over time due to progress in endovascular techniques and the expertise of operators, as well as technological advances that have allowed improvement in long-term outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…3 Patients with multiple aneurysms have higher mortality and significantly poorer outcomes than those with a single aneurysm. 4…”
Section: Introductionmentioning
confidence: 99%
“…In patients with unruptured mirror aneurysms, single-stage treatment of multiple aneurysms (if technically feasible) is advantageous to avoid second-round of general anesthesia, to eliminate the risk of rupture without delay, and to reduce hospitalization costs ( 35 ). Other reports have indicated that single-stage treatment is safe and effective in this setting ( 28 36 37 38 39 ). Cho et al ( 36 ) reported single-stage coil embolizations of 371 multiple aneurysms, performed in acceptable time intervals with few complications.…”
Section: Discussionmentioning
confidence: 91%
“…In cases of MIA, the risk of rupture is relatively high, all aneurysms in need of treatment should be treated as soon as possible; however, as mentioned above, there are no speci c guidelines for this process [7,16,25]. If possible, all of the aneurysms should be treated endovascularly [3,21]. However, there is no reason to avoid one stage operation if multiple lesions can be operated simultaneously [25].…”
Section: Discussionmentioning
confidence: 99%